Audit Judgment Memediasi Locus of Control dan Perilaku Etis Auditor Berdimensi Spiritual pada Kualitas Audit - Bawantari, Ni Putu Ayu; Wirakusuma, Made Gede; Mimba, Ni Putu Sri Harta; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2022)
This study aims to examine the effect of Locus of Control and ethical behavior based on Tat Twam Asi, Tri Kaya Parusudha and Karmaphala on Audit Quality, as well as to examine the role of Audit Judgment in mediating the effect of Locus of Control, ethical behavior based on Tat Twam Asi, Tri Kaya Parusudha and Karmaphala on audit quality. The study was conducted at the Public Accounting Firm (KAP) in Bali Province using primary data obtained from questionnaires. The method of determining the sample using the saturated sample technique with respondents obtained as many as 45 auditors. The data analysis technique used is path analysis test. The results showed that Locus of control, ethical behavior based on Tat Twam Asi, Tri Kaya Parisudha, Karmaphala and Audit Judgment each had a significant positive effect on Audit Quality. Audit judgment is able to mediate the influence of Locus of control, ethical behavior based on Tat Twam Asi, Tri Kaya Parisudha, Karmaphala on audit quality. Keywords: Locus of control; Ethical Behavior; Audit Judgment; Audit Quality.